Quality-of-life issues and symptoms reported by patients living with haematological malignancy: a qualitative study. (October 2020) - Goswami, Pushpendra; Oliva, Esther N.; Ionova, Tatyana; Else, Roger; Kell, Jonathan; Fielding, Adele K.; Jennings, Daniel M.; Karakantza, Marina; Al-Ismail, Saad; Collins, Graham P.; McConnell, Stewart; Langton, Catherine; et al.
Background: Our aim was to identify health-related quality-of-life (HRQoL) issues and symptoms in patients with haematological malignancies (HMs) and develop a conceptual framework to reflect the inter-relation between them. Methods: A total of 129 patients with HMs were interviewed in a UK multicentre qualitative study. All interviews were audio recorded, transcribed and analysed using NVivo-11. Results: Overall, 34 issues were reported by patients and were grouped into two parts: quality of life (QoL) and symptoms. The most prevalent HRQoL issues were: eating and drinking habits; social life; physical activity; sleep; and psychological well-being. Furthermore, most prevalent disease-related symptoms were: tiredness; feeling unwell; breathlessness; lack of energy; and back pain. The most prevalent treatment side effects were: tiredness; feeling sick; disturbance in sense of taste; and breathlessness. Conclusions: Both HMs and their treatments have a significant impact on patients' HRQoL, in particular on issues such as job-role change, body image and impact on finances.